Asthma in the elderly. (June 2010) - Antonelli-Incalzi, Raffaele; Corsonello, Andrea; Pedone, Claudio; Battaglia, Salvatore; Bellia, Vincenzo
Asthma is frequent among older people. Nevertheless, under-recognition, misdiagnosis and under-treatment are still relevant issues. We aim to provide an overview of epidemiology of asthma in the elderly, and a thorough description of its pathology and clinical presentation, with special emphasis on the distinction of late versus early-onset asthma. We also discuss selected treatment topics of special interest for older patients, such as compliance with therapy and ability with the inhalers, which are basic to the success of the prescribed therapy. Finally, we suggest that multidimensional geriatric assessment of older asthmatics could help in tailoring the therapy to the individual needs and capacity.